Triple A-Site Cation Mixing in 2D Perovskite-Inspired Antimony Halide Absorbers for Efficient Indoor Photovoltaics - Lamminen Noora; Grandhi Gopal Krishnamurthy; Fasulo Francesca; Hiltunen Arto; Pasanen Hannu; Liu Maning; Al-Anesi Basheer; Efimov Alexander; Ali-Löytty Harri; Lahtonen Kimmo; Mäkinen Paavo; Matuhina Anastasia; et al. (John Wiley and Sons Inc, 2025)
Antimony-based perovskite-inspired materials (PIMs) are solution-processable halide absorbers with interesting optoelectronic properties, low toxicity, and good intrinsic stability. Their bandgaps around 2 eV make them particularly suited for indoor photovoltaics (IPVs). Yet, so far only the fully inorganic Cs3Sb2ClxI9−x composition has been employed as a light-harvesting layer in IPVs. Herein, the first triple-cation Sb-based PIM (CsMAFA-Sb) in which the A-site of the A3Sb2X9 structure consists of inorganic cesium alloyed with organic methylammonium (MA) and formamidinium (FA) cations is introduced. Simultaneously, the X-site is tuned to guarantee a 2D structure while keeping the bandgap nearly unchanged. The presence of three A-site cations is essential to reduce the trap-assisted recombination pathways and achieve high performance in both outdoor and indoor photovoltaics. The external quantum efficiency peak of 77% and the indoor power conversion efficiency of 6.4% are the highest values ever reported for pnictohalide-based photovoltaics. Upon doping of the P3HT hole-transport layer with F4-TCNQ, the power conversion efficiency of CsMAFA-Sb devices is fully retained compared to the initial value after nearly 150 days of storage in dry air. This work provides an effective compositional strategy to inspire new perspectives in the PIM design for IPVs with competitive performance and air stability.